2-(4-Methylphenyl)quinoline-4-carboxylic acid - Raed A. Al-Qawasmeh; Monther A. Khanfar; Musa H. Abu Zarga; Murad A. AlDamen (Acta Crystallographica Section E, 2012)
In the title compound, C17H13NO2, the dihedral angle between the plane of the carboxy group and the quinoline mean plane is 45.05 (13)°, and that between the toluene ring mean plane and the quinoline mean plane is 25.29 (7)°. In the crystal, molecules are linked via O—H....N hydrogen bonds, forming chains propagating along the b-axis direction. These chain are linked via C—H...O interactions, forming two-dimensional networks lying parallel to the ab plane.